Answer:
f(x + 2) = 3x + 2
Step-by-step explanation:
Simply replace wherever you find x in the function f(x) with (x + 2), like so:
f(x + 2) = 3(x + 2) - 4
f(x + 2) = 3x + 6 - 4
f(x + 2) = 3x + 2
It's looking for the measures
m<F + m<G = 180°
(4x)° + (8x)° = 180°
12x = 180°
÷12 ÷12
x = 15
check your work
m<F + m<G = 180°
(4x)° + (8x)° = 180°
4(15)° + 8(15)° = 180°
60° + 120° = 180°
What is 3 times the number?
3*66 = 198
Answer:
C
Step-by-step explanation:
Bro don’t trust me
Answer:
(3, 6)
yw
Step-by-step explanation: